The effect of social environment on bird song: listener-specific expression of a sexual signal. (5th March 2021) - Jablonszky, Mónika; Zsebők, Sándor; Laczi, Miklós; Nagy, Gergely; Vaskuti, Éva; Garamszegi, László Zsolt
Abstract: Animal signals should consistently differ among individuals to convey distinguishable information about the signalers. However, behavioral display signals, such as bird song are also loaded with considerable within-individual variance with mostly unknown function. We hypothesized that the immediate social environment may play a role in mediating such variance component, and investigated in the collared flycatcher ( Ficedula albicollis ) if the identity and quality of listeners could affect song production in signalers. After presenting territorial males with either a female or male social stimulus, we found in the subsequent song recordings that the among-stimulus effects corresponded to non-zero variance components in several acoustic traits indicating that singing males are able to plastically adjust their songs according to stimulus identity. Male and female stimuli elicited different responses as the identity of the female stimuli affected song complexity only, while the identity of male stimuli altered also song length, maximum frequency, and song rate. The stimulus-specific effect on song in some cases decreased with time, being particularly detectable right after the removal of the stimulus and ceasing later, but this pattern varied across the sex of the stimulus and the song traits. We were able to identify factors that can explain the among-stimulus effects (e.g., size and quality of the stimuli) with roles that also varied among song traits. Our results confirm that the variable social environment can raise considerable variation in song performance, highlighting that within-individual plasticity of bird song can play important roles in sexual signaling. Abstract : Many animals produce individual-specific signals when communicating with others, but we know relatively little about why such traits also vary within individuals. We demonstrate that males of the collared flycatcher can adjust their songs depending on the identity of their audience, and that several features of song are altered when different male (suggesting opponent-specific investment into territorial aggression) or female (indicating potential male mate choice) stimuli are present in the vicinity.